The THE EFFECT OF KERSEN (Muntingia calabura L.) LEAF EXTRACT NANOGEL ON STOMATITIS - Ariyati Retno Pratiwi; Linda Risalatul Muyasaroh (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: Recurrent aphthous stomatitis (RAS) is common painful mucosal condition affecting the 5%-60% world’s population and become the third largest oral disease in Indonesia. Despite their high prevalence, RAS treatment is currently still dominated by the use of chemicals that scientifically have adverse side effects. Therefore, it is necessary to develop new approach using herbal product with no side effects. This literature review summarizes the potential of kersen leaf extract (Muntingia calabura L.), its dosage forms, and the possibility using nanotechnology that can speed up the drug delivery process. Objective: to determine the possibility effect of nanoparticle cherry leaf extract in gel form on decreasing number of macrophages and stimulating collagen in stomatitis. Methods: literature search using the PRISMA method with Science Direct, PubMed, Scielo, NCBI, Research gate, and Google Scholar databases of 1107 articles with keywords “Muntingia calabura L. leaves extract”, “nanogel”, “flavonoid”, “quercetin”, “fisetin”, “macrophage”, “collagen”, “soft tissue healing process” and “recurrent aphthous stomatitis”. The results of the literature selection found 22 articles. Results: flavonoids in cherry leaf extract can reduce the number of macrophages and increase collagen stimulation. The mechanism of action begins by inhibiting the production of pro-inflammatory cytokines, inhibiting macrophage migration and adhesion, stimulating the production of growth factors by macrophages for collagen synthesis, and decreasing collagenase. Nano gel form may increase retention time and drug penetration. Conclusion: Nanogel based cherry leaf extract may reduce the number of macrophages and stimulating collagen in minor RAS.